Air pollutant emissions from economic sectors in China: A linkage analysis. (June 2017) - Wang, Yuan; Lai, Nan; Mao, Guozhu; Zuo, Jian; Crittenden, John; Jin, Yi; Moreno-Cruz, Juan
Highlights: HEM method based on SRIO and MRIO model is proposed to analyze embodied flows for air pollutants. The emissions data were retrieved from the national pollution census data of China. Major embodied air pollutant emissions flows among sectors and regions of China were revealed. Market-oriented measures were suggested to coordinate various sectors and regions. Abstract: We employ the Hypothetical Extraction Method (HEM) using the Input-Output (IO) table and emissions data for China in 2010 to map flows of embodied air pollutant emissions. The results showed that the Construction sector (28.21% of SO2, 29.84% of NOx, 34.74% of Soot, 39.62% of Dust) dominates other sectors in terms of demand embodied emissions, followed by the Machinery Manufacturing (20.63% of SO2, 19.20% of NOx, 18.03% of Soot, 24.05% of Dust) and Service sectors (13.86% of SO2, 13.18% of NOx, 12.67% of Soot, 10.09% of Dust). The Power & Gas (48.98%, 60.45% and 30.66% of SO2, NOx, Soot emissions, respectively), Nonmetal Products (26.87% of Dust) and Metal Mining, Smelting & Pressing (29.51% of Dust) sectors, which provide electricity, steel, and cement and so on, were significant contributors to direct air pollutant emissions. The largest inter-sector flow of SO2 emissions was from the Power & Gas sector to Construction sector (2301.3 kt). Meanwhile, the largest inter-sector flow of industrial dust emissions was from Nonmetal Products to Construction sector (1560.0 kt). From the regional perspective, Hebei and Shanxi provinces were the main sources of output emissions in China, with their industrial output dominated by energy (mainly coal) and heavy industry. Based on our findings, we suggest a few strategies to control air-pollution in China: (1) designing differentiated sectoral control strategies by considering supply chain; (2) establishing a regional responsibility sharing mechanism for air pollutants emissions; and (3) using pricing mechanisms to implement internalize the emissions along the supply chain.